Improving knowledge of street food vendors through an educational intervention in Kandy district, Sri Lanka - Wickrematilake, M. S. K.; Arnold, S. M.; Karthikeyan, P.; Jayathilake, A. D. N. (International Journal of Research in Medical Sciences, 2022)
Background: Street food sector plays an important role in urban areas of many developing countries in catering to the needs of the urban population. Contamination of ready to eat food and beverages sold by street food vendors rendering them unacceptable for human consumption has become a global problem. The aim of this study was to evaluate the effectiveness of providing a health educational programme in improving knowledge related to food safety on street food vendors. Methods: Study used a quasi-experimental pre-test, post-test design. Evaluation instruments consisted of a questionnaire and a checklist. A total number of 427 street food vendors were included. A visual educational intervention was developed to provide training to all vendors in the intervention area. The study areas covered were method of food contamination, personal hygiene, safe food handling of potentially hazardous street vended food and time temperature control. Results: The results of the pre intervention survey showed that the baseline knowledge was poor. Vendors had unfavorable views particularly towards available facilities and support services. It was revealed that over 50% of the study population had received information on safe food handling though public health inspectors. Post intervention showed knowledge had improved significantly in the intervention group in all subject areas, when compared to control group (p<0.001). Conclusions: Health education intervention was effective in improving knowledge of the street food vendors in safe food handling practices and food borne disease prevention.